Contemporary Literary Criticism: The Challenges of Democratisation - Satkauskytė, Dalia (Colloquia, 2023)
The aim of this article is to discuss the forms of contemporary Lithuanian literary criticism in the context of more general cultural processes. The current situation, which still tends to be described as crisis, is brought about not only by the structure of the national literary field, the specifics of its historical development, or the local cultural policy, but also by universal factors, such as the epistemic, social, and institutional uncertainty that characterises professional literary criticism in general, and the so-called democratisation of culture, which has been accelerated by the emergence of social networks. The latter provide an opportunity for everyone to express their value judgements, disrupting the established hierarchies of critical evaluation and deepening the crisis of authority. This factor together with the meritocratic model that has taken root in the media, along with the commercialisation of publishing policy creates the conditions for the emergence of new ways of talking about literature, or what is known as ‘non-professional literary criticism’. Drawing on theory of New Formalism, I discuss the main types of professional and non-professional literary criticism, and their affordances, which foresees the social and cultural uses of literary criticism.